Islamic venture capital – issues in practice - Anwer, Zaheer; Asadov, Alam; Mustaffa Kamil, Nazrol Kamil; Musaev, Mehroj; Refede, Mohd (Emerald Group Publishing Limited, 2019)
Purpose – This paper aims to explore the structure and underlying contracts of Islamic venture capital (IVC) and to evaluate its prospects. VC can be perceived as an investment vehicle possessing most of the desirable attributes of a Sharīʿah-compliant investment vehicle. There are certain issues involved in the formation, operations and exit strategies of these investments that are discussed in detail in this paper. Design/methodology/approach – A detailed review of relevant literature is performed to identify how IVC investments can bemade and how related issues may be resolved. Findings – IVC investment has potential of incorporating Sharīʿah-compliant investment modes. Additionally, it may offer higher than average returns. These attributes can be desirable for Islamic finance industry that is currently in need of equity-based financing products. The major causes of lesser growth of IVC investments are lack of awareness among the investors and the absence of viable investment opportunities for small- and medium-scale investors. IVC may attract general public if established after extensive research aimed at introducing innovative products. Originality/value – This paper provides an overview of a truly Sharīʿah-compliant investment vehicle, furnishes a synthesis of various suggestions made by industry and academia and suggests viable solutions for valuation, risk management and exit strategies.